Między uniwersytetem a szkołą. Jak przygotować studentów specjalności nauczycielskiej do współczesnego kształcenia językowego - Rypel, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The purpose of this article is to show the role of the university in the transfer of knowledge and to prepare future teachers to transfer this knowledge at school. This is an extremely important problem due to contemporary cultural and social changes causing very dynamic language changes. The methods used to describe the language are changing as well. The language education model is already anachronistic in Polish schools because it doesn’t respond to this evolutionm which is why universities must prepare future teachers to react to changes on their own.